Manta de Petrolina - PE: uma alternativa para agregar valor à carne ovina - Pedrosa, Nely de Almeida (2010)
The manta ovina , a lamb meat product, is produced from the boning, salting and drying of lamb carcasses. It is a typical salted meat product from the region of Submédio do Vale does Rio São Francisco, with reference the city of Petrolina, Pernambuco Brazil. The manta ovina was evaluated in order to obtain information and establish identity patterns and product quality. In the present study was described the process, identified the potential hazards to product safety and evaluated the physicochemical (color, pH, Aw, PPC, FC, moisture, ash, proteins and lipids), microbiological (total and fecal coliforms, halophilic bacteria, Salmonella sp and Staphylococcus aureus) and sensory (appearance, aroma, flavor, texture and overall assessment) quality of manta ovina . The study was performed in three restaurants which are part of the gastronomic complex called Bodódromo , located in the city of Petrolina, in the state of Pernambuco, Brazil. The values of pH (6.22 ± 0.22), water activity (0.97 ± 0.02) moisture (69.86 ± 2.26) and protein (22.23 ± 1.96) classified the manta ovina as a perishable product, and consequently, requiring the use of other preservation methods, such refrigeration, combined with salt. The manta ovina presented 4.14 ± 2.23% fats, and about 60% of minerals (3.19 ± 0.57%) are in the form of chlorides (1.93 ± 0.64). This percentage reflects the use of salt, essential ingredient used during the processing of the product. Losses during the cooking varied significantly (P ≤ 0.05), between 14.8% and 22.4%. The measurement of texture, through instrumental (3.18 ± 0.12 Kgf) and sensory evaluation (7.44) showed that the manta ovina is a soft meat product. In sensory evaluation no significant differences (P ≥ 0.05) were detected among the samples served in the three restaurants. The mean scores were above seven points on a scale ranging from 1 to 9. It showed that the manta ovina is a meat product with appearance, flavor, tenderness and taste that pleased the consumer. Microbiological evaluation indicated the absence of Salmonella; on the other hand, Staphylococcus species showed a count of exceeding the limits prescribed by Brazilian law. This result reinforces the need for implementation and maintenance of hygienic practices to ensure a safety product. It was observed that the process used during the manta ovina preparation, involves the application of a traditional technology, salting, associated with an innovative technique of deboning, which is peculiar in region, resulting in a meat product with characteristic of great potential exploration. The results reveal a similarity in nutritional quality, physical, sensory and microbial mats, showed the similarity of production procedures used in the three restaurants. It reinforces the need to standardize the process and creation of technical regulation of identity and quality for this meat product derived.